2018
DOI: 10.1098/rsos.172477
|View full text |Cite
|
Sign up to set email alerts
|

Nest-site competition and killing by invasive parakeets cause the decline of a threatened bat population

Abstract: The identification of effects of invasive species is challenging owing to their multifaceted impacts on native biota. Negative impacts are most often reflected in individual fitness rather than in population dynamics of native species and are less expected in low-biodiversity habitats, such as urban environments. We report the long-term effects of invasive rose-ringed parakeets on the largest known population of a threatened bat species, the greater noctule, located in an urban park. Both species share prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 42 publications
1
48
0
Order By: Relevance
“…These relate mainly to competition with native cavity nesting species. For instance, the threatened greater noctule bat (Nyctalus lasiopterus) in Seville (Spain) can be forced out of roosting cavities by RNP, which has only recently been found to contribute to declining bat populations (Hernández-Brito et al 2018). Such long-term studies investigating the effect of competition on the local abundance of species are scarce in the invasion literature (Strayer et al 2006).…”
Section: Impacts Of Alien Parrots In Europe As a Function Of "Admissmentioning
confidence: 99%
“…These relate mainly to competition with native cavity nesting species. For instance, the threatened greater noctule bat (Nyctalus lasiopterus) in Seville (Spain) can be forced out of roosting cavities by RNP, which has only recently been found to contribute to declining bat populations (Hernández-Brito et al 2018). Such long-term studies investigating the effect of competition on the local abundance of species are scarce in the invasion literature (Strayer et al 2006).…”
Section: Impacts Of Alien Parrots In Europe As a Function Of "Admissmentioning
confidence: 99%
“…Several studies already demonstrated that rose-ringed parakeet can have both ecological and socio-economic impacts, notably outcompeting local species, damage to agriculture and noise pollution near roost site, but their impacts are often restricted to certain populations and some ecoregions (Turbé et al 2017). Specifically in Seville, there is strong evidence that parakeets attack, displace and even kill an endangered bat species, the Giant noctule (Nyctalus lasiopterus), due to competition over tree cavities for roosting and reproduction (Hernández-Brito et al 2018). Similar concerns exist with respect to the vulnerable Lesser kestrel (Falco naumanni, Hernández-Brito et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…With a population previously estimated at ca. 500 individuals, but now in dramatic decline due to an invasive parakeet species (Hernández-Brito et al, 2018) that is taking over the roosting holes, it was once the largest known breeding site of giant noctules (Popa-Lisseanu et al, 2008).…”
Section: Focal Species and Study Populationmentioning
confidence: 99%